Foreign Direct Investment as an Instrument for promoting Economic Development in Bangladesh - Rahman, Md. Sajedur; Ahsan, Md. Ali (Asian Business Review, 2013)
A healthy financial sector is very much crucial for economic growth, especially for economies like Bangladesh. Because, growth in Bangladesh must come largely from exports and its enterprises must, therefore, be internationally competitive. But unfortunately, Bangladesh has a financial system in which borrowers fail to repay loans, foreclosure is almost unheard of, and the government has to bail out banks. However, the Foreign Direct Investment (FDI), the most powerful weapon for accelerating economic development in Bangladesh. To attain an economic growth rate in the seven to eight percent range, investment has to be increased significantly, Because of declining levels of official development assistance in recent years and inadequate domestic savings, FDI presents opportunities for overcoming domestic resource constraints. The Board of investment (BOI) was created as market mechanism where investors can cut through red-tape associated with foreign trade and business start-ups. FDI basically helps to fill-up the capital gap and shortage of a country. Foreign Direct Investment is one of the vital forces to boost up the economy. In this study paper I would like to draw a current scenario of Foreign Direct Investment in Bangladesh. In this regard I present the most updated data, avoid the uncompleted data and use the best judgment at the time of presenting the data to better knowing the current trend about the Foreign Direct Investment in Bangladesh. The benefits of FDI in terms of physical capital formation, transfer of technology, and know-how are sufficient to justify sustaining these flows.  Capital controls are not the answer to a rising flow of FDI. Foreign Direct Investment (FDI) will help the country in further developing infrastructures, creating more employment, developing capacity, enhancing skills of the labour force of the host country through transferring technological knowledge and managerial capability. To ensure that resulting payments liabilities remain within the country’s debt-servicing capacity, it is essential to develop an effective non-intrusive reporting and monitoring system the main ingredients of which are presented in the study. JEL Classification Code:  G11, O24
Keywords: Foreign Direct Investment; Economic growth; Bangladesh